High fusion performance in Super H-mode experiments on Alcator C-Mod and DIII-D. (24th June 2019) - Snyder, P.B.; Hughes, J.W.; Osborne, T.H.; Paz-Soldan, C.; Solomon, W.M.; Knolker, M.; Eldon, D.; Evans, T.; Golfinopoulos, T.; Grierson, B.A.; Groebner, R.J.; Hubbard, A.E.; et al.
Abstract: The 'Super H-Mode' regime is predicted to enable pedestal height and fusion performance substantially higher than standard H-Mode operation. This regime exists due to a bifurcation of the pedestal pressure, as a function of density, that is predicted by the EPED model to occur in strongly shaped plasmas above a critical pedestal density. Experiments on Alcator C-Mod and DIII-D have achieved access to the Super H-Mode (and Near Super H) regime, and obtained very high pedestal pressure, including the highest achieved on a tokamak ( p ped 80 kPa) in C-Mod experiments operating near the ITER magnetic field. DIII-D Super H experiments have demonstrated strong performance, including the highest stored energy in the present configuration of DIII-D ( W 2.2–3.2 MJ), while utilizing only about half of the available heating power ( P heat 7–12 MW). These DIII-D experiments have obtained the highest value of peak fusion gain, Q DT, equiv 0.5, achieved on a medium scale ( R < 2 m) tokamak. Sustained high performance operation ( β N 2.9, H98 1.6) has been achieved utilizing n = 3 magnetic perturbations for density and impurity control. Pedestal and global confinement has been maintained in the presence of deuterium and nitrogen gas puffing, which enables a more radiative divertor condition. A pair of simple performance metrics is developed to assess and compare regimes. Super H-Mode access is predicted for ITER and expected, based on both theoretical prediction and observed normalized performance, to allow ITER to achieve its goals ( Q = 10) at I p < 15 MA, and to potentially enable more compact, cost effective pilot plant and reactor designs.